REFRAMING ADDICTION THROUGH QUR’ANIC NARRATIVES: A CONCEPTUAL SYNTHESIS OF TAFSĪR AND PSYCHOLOGY - Amri, Muhammad; Nasaruddin Umar; M. Darwis Hude (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2025)
Addiction has become a latent human problem that continues to evolve to this day. Muslims need to understand this issue comprehensively to address it effectively. One essential step is to seek guidance from the foundational source of Islamic teachings, the Qur’an. This study aims to explore the Qur’anic perspective on addiction in a specific and systematic manner. Employing a qualitative design, the research uses a thematic exegesis (tafsīr mawdhū‘ī) approach enriched by a synthetic elaboration between classical and contemporary exegetical interpretations and the psychological context of addiction. The study reveals several Qur’anic narratives that contain indications related to addictive processes, including matā‘ al-ghurūr (deceptive gratification), la‘ibun wa lahwun (play and diversion), al-tazyīn wa al-ighwā’ (adornment and seduction), al-khaṭa’ wa al-nisyān (error and forgetfulness), and ittakhadha ilāhahū hawāhu (following one’s desires as a deity). These narratives correspond to cognitive distortion, core beliefs, dopamine-driven reinforcement, loss of control, and loss of autonomy within the psychological framework of addiction. The article contributes theoretically by elucidating the Qur’anic perspective on addiction and practically by offering guidance on the mindset and personal strengths that Muslim individuals need to develop.